Research survey on iridoid and phenylethanoid glycosides among seven populations of Euphrasia rostkoviana Hayne from the Alps. (May 2017) - Mari, Angela; Ciocarlan, Alexandru; Aiello, Nicola; Scartezzini, Fabrizio; Pizza, Cosimo; D'Ambrosio, Michele
Abstract: The traditional use of extracts of Euphrasia rostkoviana to relieve ocular inflammation or infections is well documented and supported by clinical studies. Various classes of chemical compounds such as iridoids, phenylethanoids, flavonoids and hydroxycinnamic acids have been reported. The present work aims to assess the chemical diversity among seven populations of Euphrasia rostkoviana found in northern Italy. A meticulous separation of components led to the isolation and structural characterization of two previously unrecorded phenylethanoids methoxycrassifolioside and deoxycrassifolioside and one previously undescribed terpene glucoside (1 E, 6 E )-8-hydroxy-3, 7-dimethyl-octa-1, 6-dienyl 1- O -β-D-glucopyranoside. We have also identified known phenylethanoids and iridoids that are reported in this genus for the first time. Finally, a targeted quantitative analysis for the standardization of herbal preparations revealed that iridoids occur in all populations whereas the presence and the levels of rutin and phenylethanoids are highly variable. Graphical abstract: Iridoids, phenylethanoids, terpene glycosides and rutin are the main constituents of E. rostkoviana from the alpine area of Trentino, Italy. The structures of three previously undescribed compounds were established by spectroscopic methods. Highlights: A thorough phytochemical investigation of Euphrasia rostkoviana has been performed. Several iridoids, phenylethanoids, terpene glycosides and a flavonoid were identified. Two phenylethanoids and one terpene glycoside were previously undescribed. Quantitative analysis assessed the chemical diversity in seven populations from the Alps.